“matriz de evaluación a la dimensión y control de los factores críticos de riesgo referente a la prevención de lavado de activos en una entidad del sistema financiero” - González Carrión, Raúl Agustín (2010)
This project consists of four chapters where the first part will conceptually define the problems now affecting the Ecuadorian financial system for money laundering and in turn is an analysis of the impact it brings. In addition, we briefly cover the different ways to instill and promote internal control within the banking industry organizations including a brief highlight of: Law Sarbanes - Oxley, COSO, the Basel Committee's recommendations and others. ollowing this, chapter two will cover the concept and forms of money laundering within the financial sector. FIn chapter 3 and 4 show respectively the creation and implementation of a matrix that evaluates the internal processes relating to the prevention of money laundering. The matrix was based on the understanding of the rules issued by the bank board is the codification of which JB-2008-1154. The array consists of a control strategy that measures the different points of risk in an environment of control boxes. The overall structure is divided into four control components such as: organizational structure, policies and procedures, reports and reporting and training.